PSYCHOLOGICAL NOVELS OF US AND THE DEVELOPMENT OF PSYCHOLOGYSMS - Xayrulloeva, Sitora (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
Psychological novels can be found in a number of scientific publications about their origin and the psychological process in it. In world and European literature, psychological novels and the definition of psychologisms are studied in relation to the works of James Joyce and Henry James, while in Russian literature, the works of Dostoyevsky and Tolstoy reveal the deep points of the hero's psyche and the inner motives of human behavior. Novel writing or analysis of the inner world of the heroes of works of art, when it comes to Uzbek literature, started in the late 40s of the last century, but gradually became firmly established in the world of literature in the 60s. Although the psychological approach to fiction was formed in Europe, its development is closely associated with modern America today.